PENGARUH KETERAMPILAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 3 PEKANBARU - Salsabila Irianti Salsa; Sumarno; M. Yogi Ryantama Isjoni (Universitas Pasundan, 2025)
This research aims to determine the influence of entrepreneurial skills and family environment on students' interest in entrepreneurship at SMKN 3 Pekanbaru. The population in this study was class XII students with a total of 430 students and a sample of 82 students. The sampling technique uses a random sampling method. This research uses primary data obtained through questionnaires. The data analysis technique uses linear multiple regression analysis. The results of the research show that entrepreneurial skills have a significant effect on the interest in entrepreneurship of class XII students at SMKN 3 Pekanbaru, while the family environment has no significant effect on the interest in entrepreneurship of class < 0.05 and the value of the family environment variable is 0.911 > 0.05. This means that if students have high entrepreneurial skills, their interest in entrepreneurship will also be high with an increase of 0.873. Meanwhile, the family environment has no influence on interest in entrepreneurship because the increase is only 0.014.